2021
DOI: 10.18488/journal.61.2021.92.411.423
|View full text |Cite
|
Sign up to set email alerts
|

Using Padlet as a Technological Tool for Assessment of Students Writing Skills in Online Classroom Settings

Abstract: The lifestyle of humans is constantly changing due to globalisation. The demand for suitable and appropriate technological tools applicable in the teaching and learning processes is therefore increasing. The traditional method of chalk and talk in a classroom setting is slowly being replaced with Web 2.0 due to various implications. However, studies on the implications and effectiveness of these tools towards students' assessment of their learning process are lacking, especially in the writing skill. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 19 publications
2
29
0
2
Order By: Relevance
“…It has been determined that the activities prepared with Web 2.0 technologies contribute to the creation of a more effective learning environment in line with the interests and wishes of the z-generation students and to transform the learning environments into a more equipped and enjoyable one. Similarly, studies have supported that the activities carried out with web 2.0 technologies contribute to the learning level of students (Arslan & Coştu, 2021;Ergül Sönmez & Çakır, 2021;Açıkgül Fırat & Fırat, 2020;Vanichvasin, 2021;Kazazoğlu & Bilir, 2021;Egüz, 2020;Karakaş & Kartal, 2020;Bolliger & Shephard, 2017;Şahin Topelcengiz & Yıldırım, 2020;Juškeviciene & Kurilovas, 2014;Azid, Hasan, Nazarudin & Ali, 2020;Jong & Tan, 2021). With this thought, it is necessary to use in-class and extra-curricular activities prepared with web 2.0 technologies that support educational environments.…”
Section: Conclusion and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been determined that the activities prepared with Web 2.0 technologies contribute to the creation of a more effective learning environment in line with the interests and wishes of the z-generation students and to transform the learning environments into a more equipped and enjoyable one. Similarly, studies have supported that the activities carried out with web 2.0 technologies contribute to the learning level of students (Arslan & Coştu, 2021;Ergül Sönmez & Çakır, 2021;Açıkgül Fırat & Fırat, 2020;Vanichvasin, 2021;Kazazoğlu & Bilir, 2021;Egüz, 2020;Karakaş & Kartal, 2020;Bolliger & Shephard, 2017;Şahin Topelcengiz & Yıldırım, 2020;Juškeviciene & Kurilovas, 2014;Azid, Hasan, Nazarudin & Ali, 2020;Jong & Tan, 2021). With this thought, it is necessary to use in-class and extra-curricular activities prepared with web 2.0 technologies that support educational environments.…”
Section: Conclusion and Discussionmentioning
confidence: 96%
“…In Batıbay (2019) examined the educational function of the Kahoot application in a Turkish lesson; he determined that the application has a positive effect on the motivation of students by transforming the question-solving action into a game, students are actively involved in the education process, it enables peer learning, and that it offers an effective learning environment suitable for the 21st-century education system understanding. In their study, Jong and Tan (2021) examined the effects of using Padlet, one of the web 2.0 tools, on students' writing skills. They concluded that the Padlet application is suitable for use as an easy, interesting, and practical writing tool in the education process; In Padlet, the writing progress is observable and open to feedback correction; it provides a student-centered learning platform, and has a positive effect on the professional development of teachers.…”
mentioning
confidence: 99%
“…These guidelines can be convenient when teachers wish to motivate the learners and show more appreciation for them while applying the MAPL approach. Moreover, planning pedagogical tools in various forms via social media or online learning platforms is another way to keep learners motivated [75].…”
Section: Achieving Digital Equity: Mapl Through E-modulesmentioning
confidence: 99%
“…Padlet is especially useful, as students need not create an account and can participate and ask questions anonymously, which can foster uninhibited critical engagement (Deni and Zainal, 2018). For assessment, Padlet can also be used to assess students' writing skills Journal of Learning Development in Higher Education, Issue 22: Compendium October 2021 4 (Jong and Tan, 2021) and allows for students to 'grade' one another's posts with a numeric score, which can foster peer assessment (Adachi et al, 2018), A caveat that I would like to emphasise is that I had a maximum of 25 students in each of my two tutorials; thus, using Padlet in my experience was very feasible. This may be more challenging in a larger course.…”
Section: Recommendationsmentioning
confidence: 99%